2017
DOI: 10.3892/or.2017.5832
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-106a promotes cell migration and invasion by targeting tissue inhibitor of matrix metalloproteinase 2 in cervical cancer

Abstract: Abstract.Increasing evidence has demonstrated that miRNAs play a critical role in tumor development and progression. Previous studies have revealed that miR-106a is abnormally expressed in various cancers. However, its function and underlying mechanism in cervical cancer (CC) remains unknown. In this study, we confirmed that the expression of miR-106a was significantly upregulated in both CC cell lines and tissues by qRT-PCR. The increased expression of miR-106a was obviously associated with adverse prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The oncogenic role of hsa-mir-106a-363 cluster has been much less extensively studied, specifically in the context of leukemia. There are few reports indicating an oncogenic potential of miRNAs from this cluster in human malignancies [93], [94], [95]. Interestingly, Dylla and Jedlicka demonstrated the importance of the cooperative oncogenic activity of miRNAs from this cluster in Ewing sarcoma cell lines; blockade of individual miRNAs had little or no inhibitory effect on growth of the cells in contrast to the blockade of the whole cluster [94].…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of hsa-mir-106a-363 cluster has been much less extensively studied, specifically in the context of leukemia. There are few reports indicating an oncogenic potential of miRNAs from this cluster in human malignancies [93], [94], [95]. Interestingly, Dylla and Jedlicka demonstrated the importance of the cooperative oncogenic activity of miRNAs from this cluster in Ewing sarcoma cell lines; blockade of individual miRNAs had little or no inhibitory effect on growth of the cells in contrast to the blockade of the whole cluster [94].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that the enhanced motility and invasiveness of cancer cells are associated with the progression of cervical cancer (14-16). In the present study, we observed that overexpression of S100A9 promoted the proliferation and migration of cervical cancer cells, eventually facilitating EMT, which was regulated by the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis-associated protein 1 (MTA-1), matrix metalloproteinase (MMP)2, and MMP9 are important components of the matrix metalloproteinase family, which can hydrolyze intercellular matrix proteins, providing cells with the ability to metastasize [31]. Tissue inhibitor of metalloproteinases 2 (TIMP2) can inhibit MMPs, while increased expression of E-cadherin, vimentin, and collagen I protein stabilize cells [32]. The migration and invasive ability of malignant cells have previously been shown to be associated with overexpression of MTA-1, MMP2, and MMP9 and inhibition of TIMP-2 expression [3032].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue inhibitor of metalloproteinases 2 (TIMP2) can inhibit MMPs, while increased expression of E-cadherin, vimentin, and collagen I protein stabilize cells [32]. The migration and invasive ability of malignant cells have previously been shown to be associated with overexpression of MTA-1, MMP2, and MMP9 and inhibition of TIMP-2 expression [3032]. The results of this study showed that after silencing of the MYH10 gene, the expression levels of MTA-1, MMP2, and MMP9 genes and proteins were significantly down-regulated, whereas TIMP-2 was upregulated.…”
Section: Discussionmentioning
confidence: 99%